PENGUKURAN BEBAN KERJA PADA KARYAWAN NON ORGANIK DENGAN MENGGUNAKAN METODE NASA-TLX DEP. JASA BENGKEL DAN FABRIKASI DI PT. PETROKIMIA GRESIK - kholim, abdul (JUSTI (Jurnal Sistem dan Teknik Industri), 2023)
Having a focus on agro-industry, Petrokimia Gresik is required to carry out high productivity in order to meet the demand for fertilizer in Indonesia. The Workshop and Fabrication Services Department is one of the work units at Petrokimia Gresik which is responsible for carrying out the fabrication process of factory equipment which is then used by the production work unit. In all work activities in fabrication, the workload of workers and operators in the fabrication workshop is inseparable. many workers experience physical and mental complaints in every work activity because fabrication work is a fairly large environment. Associated with manual handling, noisy areas, high temperatures. From the various types of work received by the various fabrication teams, the fabrication team is required to have high skills and creativity because to meet the production targets requested by the user, workers have to work overtime and have to work more than usual hours. There are several jobs given to workers who are considered by some workers to be not in accordance with the abilities of these workers, causing mental workload and workers getting pressure from superiors. So it is necessary to measure in a study way to review the value of the workload that occurs in the pharmaceutical process. Measurement of workload using the Heart Rate approach for physiology and NASA-TLX subjectively for psychology. It was found that the highest performance dimension results with a score of 5290 in the accumulation of workload carried out on 25 respondents (all fabrication workers) in 4 worker classifications. Companies are advised to provide training or certification to workers in order to improve competence in order to obtain new work technology methods that are efficient and motivating. Plus workers can be more active, dynamic, and intense towards the specified classification field. In line with the fabrication process can more optimally support the company’s production. Keywords : Workload, Subjective Measurement, Heart Rate, NASA-TLX